Electronic structure and spectroscopy of the cycloheptatrienyl molybdenum halide complexes [MoBrL2(η-C7H7)]n+ (L2 = 2CO, n = 0; L2 = 2, 2′-bipyridyl, n = 0 or 1). (28th January 2015) - Roberts, Kathryn A.E.; Brown, Neil J.; Roberts, Hannah N.; McDouall, Joseph J.W.; Low, Paul J.; Whiteley, Mark W.
Graphical abstract: Electronic structure calculations (DFT, B3LYP/Def2-SVP) on the half-sandwich cycloheptatrienyl molybdenum complexes [MoBrL2 (η-C7 H7 )] (L2  = 2 CO or 2, 2′-bipyridyl) reveal that in each case the HOMO features significant metal d z 2 character but the composition of the LUMO is L2 dependent. TD-DFT methods have been employed to analyse the experimental UV–Vis electronic absorption spectra of these complexes. Abstract: DFT calculations at the B3LYP/Def2-SVP level have been conducted on the half-sandwich cycloheptatrienyl molybdenum complexes [Mo(CO)3 (η-C7 H7 )] +, [1 ] + and [MoBrL2 (η-C7 H7 )] n + (L2  = 2 CO, n  = 0, 2 ; L2  = bpy, n  = 0, 3 ; L2  = bpy, n  = 1, [3 ] + ; bpy = 2, 2′-bipyridyl). In all cases, strong δ-bonding interactions operate between the e2 level of the C7 H7 ring and metal d xy and d x 2 - y 2 orbitals resulting in a metal-centred HOMO with substantial d z 2 character in the 18-electron, closed shell systems. The experimental electronic UV–Vis spectra of [1 ] +, 2 and3 are accurately reproduced by TD-DFT methods. For complexes2 and3, assignments made with the assistance of calculated spectra indicate that absorptions in the region 390–770 nm originate from a series of MLCT (metal–ligand charge transfer) or ILCT (inter-ligand charge transfer) transitions in which carbonyl, C7 H7 and 2, 2′-bipyridyl ligands act as acceptor systems from the metal or mixed metal and bromide donor groups. The metal-centred, one-electron oxidation of3 to3 [PF6 ] results in almost complete quenching of the visible region MLCT/ILCT absorptions of3 and replacement with weak transitions probably arising from bromide to metal LMCT (ligand to metal charge transfer) processes.